Charge Injection Device Performance in Low-Earth Orbit. (18th March 2020) - Batcheldor, D.; Sawant, S.; Jenne, J.; Ninkov, Z.; Durrance, S.; Bhaskaran, S.; Chapman, T.
Abstract: Charge Injection Devices (CIDs) have demonstrated direct contrast ratios in excess of 1:20 million from sub-optimal ground-based astronomical observations. CIDs are therefore interesting prospects for obtaining direct images from a host of high contrast ratio celestial scenes. However, while CIDs are capable of much deeper contrast ratios, potentially exceeding 1:1 billion, they do not address the Inner Working Angle (IWA) problem. If the Point-Spread Function (PSF) of a bright target is not well understood and accounted for, then the IWA will be large and nearby faint objects, like exoplanets, will be challenging to observe regardless of the detector used. As Earth's atmosphere is a major contributor to the variability of a PSF, high contrast ratio imaging with small IWAs will be best achieved in space. Therefore, if CIDs are to be used on future space-telescopes, they must be flight qualified in the space environment and shown to be at the appropriate Technology Readiness Level (TRL). Here we report the results of an 8 months CID technology demonstration mission that used the Nano-Racks External Platform mounted to the Kibo Exposed Facility on-board the International Space Station . Over the course of the 236 days mission we find no significant on-orbit changes of CID performance in terms of dark current, linearity, read noise, and photon transfer efficiency. As a result, CIDs are now space-qualified to TRL-8 and can be considered for future space telescopes.